Numerical simulation of thermoelastic contact problem of disc brake with frictional heat generation (2012)
This work models the heat generation and dissipation in a disc brake during braking and the following release period. The model simulates the braking action by investigating both the thermal and elastic actions occurring during the friction between the two sliding surfaces, represented by the maximum temperature on the contact surface. Brake pad and disc were selected, and parameters set to certain values from existing literatures. Three dimensional thermomechanical analysis model of the disc brake system was created, and governing dynamics and heat equations described. Comparison was also made of the selected pad material (aramid) with that of asbestos to ascertain its viability as an effective substitute and to improve conceptual designs. The verification and application of the simulation software showed that the models and technique adopted in this work are efficient and appropriate for numerical simulation of brake disc which could be employed to guarantee safety and durability of the braking system.